4-Formylazetidin-2-ones, synthon for the synthesis of (2R,3S) and (2S,3R)-3-amino-2-hydroxydecanoic acid (AHDA) - Shirode, N. M.; Deshmukh, A. R. A. S. (Tetrahedron, 2006)
An efficient synthesis of 3-amino-2-hydroxydecanoic acid (AHDA), a nonproteinogenic amino acid, using enantiopure 3-benzyloxy-4-formylazetidin-2-one as a building block is described. Both the enantiomers of AHDA have been synthesized from the corresponding enantiomer of 3-benzyloxy-4-formylazetidin-2-one in good yield and optical purity. (c) 2006 Published by Elsevier Ltd.
Keywords: Amino acids; azetidin-2-ones; Staudinger reaction; stereoselective synthesis; Wittig reaction

Gamma-heteroatom directed stereocontrolled staudinger cycloaddition reaction of vinylketenes and imines - Shaikh, Aarif L.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron Letters, 2006)
Vinylketenes possessing a gamma-heteroatom, on Staudinger cycloaddition reaction with imines gave trans-3-vinyl-beta-lactams in very good yields. The vinyl side chain stereoselectively adopts the Z-configuration in the transition state to stabilize the vinylketene and produces, exclusively, trans-3-vinyl-beta-lactams. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: imines; Staudinger reaction; stereoselective synthesis; vinylketenes

Stereoselective synthesis of spiro-beta-lactams using D-(+)-glucose derived chiral pool: remarkable influence of the torquoelectronic effect - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron, 2007)
Diastereoselective synthesis of spiro-beta-lactams via [2+2] cycloaddition reaction of imines and chiral ketenes is described. The chiral ketene was prepared from commercially available, inexpensive D-glucose. Although, theoretically four diastereomers are possible, the reaction yielded only two diastereomers stereoselectively in good to moderate yields. The stereochemical outcome of the reaction was in accordance with the torquoelectronic model. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: imines; ketenes; spiro-beta-lactams; Staudinger reaction; stereoselective synthesis